Building a sustainable east – west dialogue on teaching and learning: The fusion of lesson and learning studies - Wood, Keith (Journal of Research, Policy & Practice of Teachers and Teacher Education, 2018)
This paper reports on the growth of the World Association of Lesson Studies (WALS) and the international dialogue that it sustains. In particular, it outlines the features of Learning Study; the hybrid version of Lesson Study developed through a sustained East – West dialogue of more than a decade, and refers the reader to some of the key publications that have contributed to it. The Variation Theory used in Learning Study in the Asia-Pacific region was developed in Europe from the phenomenographic research approach to learning (Marton and Booth, 1997) to explain the conditions necessary for the design of effective learning situations. Many parallels have since been observed. The Learning Study approach to design is illustrated here and its strengths and challenges identified. Its potential as a teacher action research, professional development strategy is discussed. The intention of this paper is to invite the reader to join the dialogue.